STRUKTUR, FUNGSI, DAN MAKNA SHUUJOSHI YONE, WA, DAN KASHIRA DALAM KOMIK SCHOOL RUMBLE VOLUME 1-10 KARYA JIN KOBAYASHI - Agus Kartika, I Ketut; Anggraeny, Renny; Gorethy Nie Nie, Maria (Humanis, 2017)
This research describes the form, functions, and contextual meaning of shuujoshi yone, wa, and kashira found in the Japanese comic School Rumble volume 1-10 written by Jin Kobayashi. The obtained data were analyzed using descriptive analysis method. This research applied the theory of syntax by Verhaar (2010) and theory of contextual meaning by Pateda (2001). The shuujoshi yone, wa, and kashira in sentence always follow the verbs, adjectives, and noun. There are four functions of shuujoshi yone, wa, and kashira. Contextual meaning from these shuujoshi can be seen from three context, that is situation context, purpose context, and speaker’s moods contexts.
Keywords: shuujoshi, yone, wa, kashira